The Influence of Financial Literacy, Mobile Banking, and Financial Management on the Financial Performance of MSMEs in Melawi Regency - Tria Ardika; Heni Safitri (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
Banking and Financial Management on the Financial Performance of Micro, Small, and Medium Enterprises (MSMEs) in Melawi Regency. This research uses a quantitative approach with survey methods to collect data from MSME owners in the area. The focus of the research is to explain and identify the association between financial literacy, use of Mobile Banking services, financial management, and financial performance of MSMEs.Data was collected through questionnaires distributed to selected samples of MSME owners in Melawi Regency. Regression analysis is used to evaluate the extent to which financial literacy, mobile banking, and financial management variables can explain variations in MSME financial performance. The research results are expected to contribute to understanding the impact of financial literacy, use of Mobile Banking, and financial management on the financial performance of MSMEs. It is hoped that these findings will provide valuable information for business people, financial institutions and local governments in designing more effective MSME development strategies in Melawi Regency. This research confirms that financial literacy, mobile banking and financial management have an important role in supporting the growth and sustainability of MSMEs, with the implication that increasing financial understanding and adaptation to banking technology can improve the financial performance of MSMEs at the local level.